2019
DOI: 10.1371/journal.pone.0219918
|View full text |Cite
|
Sign up to set email alerts
|

Great expectations, inconvenient truths, and the paradoxes of the dog-owner relationship for owners of brachycephalic dogs

Abstract: Popularity of brachycephalic (flat-faced) dog breeds is increasing internationally despite well-documented intrinsic health and welfare problems associated with their conformation. Given this apparent paradox, greater understanding of the expectations and reality for brachycephalic dog owners and factors driving the dog-owner bond are needed. This study reports a large-scale online survey with valid responses from 2168 owners of brachycephalic dogs (Pugs: n = 789, median age of dogs 2.5 years; French Bulldog: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(179 citation statements)
references
References 44 publications
10
139
0
14
Order By: Relevance
“…In contrast, the volatility of German Shepherds was very low (v i = -3) even though the number of registrations of German Shepard puppies is the highest in 20 years among the breeds in our study population. This observation is in accordance with the results obtained by other authors that found that social influence has been more important than functional traits (e.g., health and trainability) in determining owners' choice of a breed [18,36,39].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the volatility of German Shepherds was very low (v i = -3) even though the number of registrations of German Shepard puppies is the highest in 20 years among the breeds in our study population. This observation is in accordance with the results obtained by other authors that found that social influence has been more important than functional traits (e.g., health and trainability) in determining owners' choice of a breed [18,36,39].…”
Section: Discussionsupporting
confidence: 93%
“…Owner expectations of what is 'normal' or 'good' behaviour for their breed is likely to influence the likelihood of veterinary presentation for perceived undesirable behaviour. In a recent study of brachycephalic ownership experiences, one-fifth of owners reported their dog behaved better than expected, and two-thirds met expectations, suggesting that the majority of brachycephalic dog owners appear satisfied with their dog's behaviour 80 . Studies that explore actual behavioural differences (positive or negative traits) between brachycephalic and non-brachycephalic breeds are in their relative infancy compared to studies on physical health differences.…”
Section: Discussionmentioning
confidence: 91%
“…However, the views of this subset of owners are valuable, and give further understanding of the challenges owners might face and have substantially added to understanding above and beyond the ndings of previous quantitative studies in this area. Equally, the majority of participants in this study were female, which could be due to women being more willing to participate or viewing themselves as having a more signi cant caregiving role, but this high proportion of female respondents has also been noted in previous relevant studies (17,19,26,37). Another limitation was that the diagnosis of idiopathic epilepsy was reliant on owner reporting.…”
Section: Discussionmentioning
confidence: 80%